Surgical Orthodontic Treatment of Severe Skeletal Class II - Fahad F. Alsulaimani; Maisa O. Al-Sebaei; Ahmed R. Afify (Hindawi Limited, 2013)
This paper describes an adult Saudi male patient who presented with a severe skeletal class II deformity. The case was managed with a combination of presurgical orthodontic treatment followed by a double jaw orthognathic surgery and then another phase of orthodontic treatment for final occlusal detailing. Extraction of the four first premolars was done during the presurgical orthodontic phase of treatment to decompensate upper and lower incisors and to give room for surgical setback of the maxillary anterior segment. Double jaw surgery was performed: bilateral sagittal split ramus osteotomy for 8 mm mandibular advancement combined with three-piece Le Fort I maxillary osteotomy, 6 mm setback of the anterior segment, 8 mm impaction of the maxilla, and 5 mm advancement genioplasty. Although the anteroposterior discrepancy and the facial convexity were so severe, highly acceptable results were obtained, both esthetically as well as occlusally.